Perbedaan antara Kadar Leukosit Maternal pada Ketuban Pecah Dini Persalinan Preterm dengan Aterm di Rumah Sakit Umum Daerah Sanjiwani Gianyar - Komang Putri Indrasuari; I Made Pariartha; Made Dharmesti Wijaya (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Premature rupture of membranes (PROM) is the rupture of the membranes before delivery. PROM occurs at 37 weeks gestation or more and PPROM occurs before 37 weeks gestation. One of the risk factors for PROM is infection that begins with the entry of bacteria into the intraamnion from the ascending urogenital tract or infection of systemic origin. Elevated leukocyte levels are a sign of infection. This study aims to determine the difference between maternal leukocyte levels of PROM and PPROM. The research design used was descriptive analytic method with a cross sectional approach. The sampling technique used is simple random sampling method. Data were analyzed using the Saphiro Wilk test for normality and the Independent Sample T Test to compare the difference in the mean of the two different groups. The results of the Saphiro Wilk test obtained values of 0.107 and 0.086, respectively (P>0.05), which means that the data is normally distributed. The results of the independent sample t-test showed a significance value of p=0.008. Therefore, it can be concluded that there is a difference in the number of leukocytes between PROM and PPROM at the Sanjiwani Regional General Hospital, Gianyar.